Depreciation Accounting Standards: A Comparative Study of Accounting Standards on Depreciation in India and United Kingdom - Singh, Rupinder (Indian Journal of Finance, 2009)
Accounting is treated as language of business, which communicates the financial results of an enterprise to different interested parties by means of financial statements. Accounting bodies have developed certain rules, which are to be followed by the accountants in the preparation of financial accounts. However these rules have to be used with a reasonable degree of flexibility after considering the specific circumstances of a particular enterprise and also economic environment, social needs, legal requirements and technological developments. Though these accounting rules are not rigid like physical sciences, yet the accountants have to operate within the bounds of rationality, objectivity and consistency. Because of these flexibilities, many diverse practices have been recognized over a period of years. The need for harmonizing these diverse policies and practices was felt in order to make the financial statements more understandable and comparable. It was felt that if some standard accounting policies or practices were prescribed, it would narrow down the differences. This can be considered as a genesis for setting the accounting standards. Accounting standards are the policy documents issued by a recognized expert accountancy body relating to various aspects of measurement, treatment and disclosure of accounting transactions and events. The main purpose of accounting standards is to standardize diverse accounting policies with a view to eliminate, to the extent possible, incomparability of financial statements information and provide a set of standard accounting policies, valuation norms and disclosure requirements to discourage pursuance of accounting policies which are not in conformity with generally accepted accounting policies. In different countries, there are different standard setting bodies.